Significance of flexion range of motion as a risk factor for kyphotic change after cervical laminoplasty. (June 2020) - Fujishiro, Takashi; Nakano, Atsushi; Yano, Toma; Nakaya, Yoshiharu; Hayama, Sachio; Usami, Yoshitada; Nozawa, Satoshi; Baba, Ichiro; Neo, Masashi
Highlights: Kyphotic deformity is a rare but serious complication after cervical laminoplasty (CLP). The recognition of the risk factor is essential for proper patient selection to achieve successful surgical outcomes. Flexion range of motion is a useful predictor of kyphotic change after CLP. For patients with preoperative fROM exceeding 40°, CLP should be carefully indicated. Abstract: Kyphotic deformity is a rare but serious complication after cervical laminoplasty (CLP), and several studies have investigated its predictors. In these studies, a kyphotic Cobb angle of 0°–5° between C2 and C7 at a certain postoperative time-point was often used to detect kyphotic deformity. However, studies considering the amount of cervical lordosis loss compared to the preoperative measurement are scarce. This study aimed to elucidate risk factors for kyphotic change after CLP by comparing patients with and without marked loss of cervical lordosis postoperatively. The study population was divided into seven patients with and 92 patients without a loss of >10° of the C2-7 angle during the follow-up period compared to the preoperative measurements [cervical lordosis loss (CLL) group and no CLL (NCLL) group, respectively]; demographic characteristics, surgical information, preoperative radiographic sagittal parameters of the cervical spine, and posterior paravertebral muscle morphology evaluated by magnetic resonance imaging were compared between two groups. A univariate analysis revealed that the CLL group had significantly greater flexion range of motion (fROM) than the NCLL group (43.0° vs. 25.8°, P  < 0.001); however, no statistical significance was identified for other parameters. The fROM had a high capacity to discriminate between the CLL and NCLL groups (area under the receiver-operating characteristic curve, 0.880; P  < 0.001; 95% confidence interval, 0.589–0.974) with an optimal cutoff point of 37°. This study suggests that greater fROM is a risk factor for the development of kyphotic changes after CLP. For patients with preoperative fROM exceeding 40°, CLP should be carefully indicated.